Effect of integrated perioperative rehabilitation intervention under the fast-track surgery concept on stress and complications in patients undergoing craniocerebral injury surgery - Zhao, Bin; Wang, Heng (Frontiers in Surgery, 2023)
Objective To observe the intervention effect of integrated medical and nursing perioperative rehabilitation intervention under the concept of FTS on the occurrence of stress and postoperative complications in patients undergoing craniocerebral injury surgery. Methods 70 patients with TBI admitted to our neurosurgery department from January 2019- December 2021 were selected for the study, and were divided into general group and FTS group according to the random number table method, with 35 cases in each group. In the general group, basic perioperative nursing care measures were used for intervention, and in the FTS group, the medical and nursing integrated perioperative rehabilitation model under the FTS concept was used for intervention on the basis of the general group. The two groups of patients were compared in hemodynamic indexes (heart rate, mean arterial pressure), stress hormone levels (CORT, GLU, E), changes in motor neurological function (GCS score, NHISS score, FMA score), occurrence of postoperative complications (infection, pressure sores, rebleeding, central hyperthermia), short-term quality of life (SF-36) before and after the intervention. Results After the intervention, the levels of HR, MAP, COR, GLU, and E were significantly lower in the FTS group than in the general group (all P<0.05). After the intervention, the Fugl-Meyer score and Barthel index score of upper and lower extremities in both groups were significantly higher than those before the intervention, and the FTS group was higher than the general group, and the difference was statistically significant (P<0.05). Short-term physical function, somatic pain, physical function, general health status, social function, energy, mental health, and emotional function scores were significantly higher in the FTS group than in thegeneral group, and all differences were statistically significant (P < 0.05). the total incidence of complications such as infection, pressure sores, rebleeding, and central hyperthermia was significantly lower in the FTS group than in the general group, and the differences were statistically significant (P < 0.05).